Hyperoxia as a driver of gut dysbiosis - Wu, Hang; Zeng, Wenxia; Dai, Ninan; Gu, Juan; He, Ying; Qin, Han; Lin, Long; Fu, Xiaoyun; Fu, Bao; Xing, Zhouxiong (Frontiers in Microbiology, 2025)
The mammalian colon lumen exists in a highly anaerobic environment (oxygen partial pressure (PO2) < 1 mmHg), which promotes the growth of beneficial obligate anaerobes (OA) while limiting the expansion of pathogenic facultative anaerobes (FA). Gut dysbiosis is associated with a wide range of human diseases, and is often characterized by an overgrowth of FA, particularly those in the Enterobacteriaceae family. Oxygen (O2) plays a crucial role in bacterial physiology and ecology, and increased O2 availability is a key driver of gut dysbiosis. O2 therapy is commonly used for hypoxic patients, either through inhalation or extracorporeal membrane oxygenation (ECMO), both of which can expose the gut to excess O2, known as hyperoxia. Hyperoxia leads to the overproduction of reactive O2 species, resulting in organ injury and worsening clinical outcomes. Viewing gut dysbiosis from an ecological perspective highlights the disruption of host mechanisms that regulate the gut microbiota, particularly in the context of antibiotic use and a western (low fiber) diet, where physiological hypoxia in the colonic epithelium is compromised. This review extends that perspective to O2 therapy in acute care, discussing the rationale and experimental evidence linking hyperoxia to gut dysbiosis, with a focus on venoarterial (VA)-ECMO support as a potential contributor. Understanding these mechanisms could help clinicians optimize O2 management during therapy.